Coordination and agility: How is the correlation in improving soccer dribbling skills? - Nurkadri; Daulay, Basyaruddin; Azmi, Fauzan (Journal Sport Area, 2021)
Investigation that was raised in this study was to improve dribbling skills. One form of training that must be done is coordination training and agility training for the players of the Tunas Muda Medan Football School (SSB TMM). Furthermore, it is expected that discoveries can be made that can improve dribbling skills with other training components for soccer players in soccer schools. This study aims to improve the skills of dribbling SSB TMM players in the city of Medan, North Sumatra Province by using coordination training and agility training. The experimental population was all SSB TMM players with a sample of 22 people. The research method used is descriptive with a correlational process, the analysis system is used to test the hypothesis which is the normality test, linearity test, and correlation test. From the end of the first hypothesis correlation test, a significance value of 0.046 <0.050 is obtained, so there is a significant relationship between coordination on the results of the ability of dribbling ball. The achievement of the second hypothesis test has a significance value of 0.037 <0.05, so there is a significant relationship between agility and the results of the ability to dribble a ball. Based on the multiple regression test, it is known that the significance is 0.037 <0.05, then H0 is not accepted and Ha is accepted. Thus, the two components of coordination and agility simultaneously have a significant relationship with the ability to dribble a ball.